Sebaran dan Kelimpahan Lipas Kayu (Panesthia angustipennis angustipennis) di Bawah Tegakan Akasia (Acacia crassicarpa) dan Hutan Alam pada Lahan Gambut - NURARIFIN, IRFAN; MUHAMMAD, AHMAD; SALBIAH, DESITA (Jurnal Riau Biologia, 2016)
Residual wood under acacia (Acacia crassicarpa) plantation forest on peatland harbors diverse insects,among which is the wood-feeding cockroaches (Panesthia angustipennis angustipennis. Blaberidae,Blattodea). This insect appears to enhance nutrient cycling through consumption and maceration ofdecaying wood. The purpose of this study was to assess the distribution and abundance of this insect inthis pulpwood plantation and nearby natural forest remnants. Sampling has been done in plantationblocks representing <1, 2-3 and 5-6 year-old stands and also in natural forest. Results showed that woodfeedingcockroaches was most frequently found (80,0 %) in 2 year-old acacia stand, whereas it was leastfrequently encountered in natural forest. Likewise, it was most abundant (9,500 individuals/ha or 0.95individuals/m2) in the former, while it was least abundant (2,500 individuals/ha or 0.25 individuals/m2) inthe latter. In general, the insect was more abundant in the plantation forest than in natural forest.Key words: Pulpwood plantation forest, residual wood, wood-feeding cockroaches .